PENGARUH TIPE LAPORAN KEUANGAN, PROFITABILITAS, LIKUIDITAS, RASIOUTANG PERUSAHAAN DAN PERGANTIAN AUDITOR TERHADAP TIMELINESS LAPORAN KEUANGAN - Siti Hamidah; Diana Fajarwati (JRAK: Journal of Accounting Research and Computerized Accounting, 2015)
The purpose of this study was to determine the effect of type of financial statements, profitability,liquidity, corporate debt ratio, and the turn of the auditor on the timeliness of financial reports. The research method is descriptive with quantitative approach. Data of this research is secondary datathat the financial statements of companies listed in the LQ-45 index over the three years from 2011 to 2013 obtainedfrom www.idx.co.id. The data were analyzed using logistic regression with SPSS 22.0 software. The results of this study indicate that the type of change of auditor of financial statements andsignificant effect while the ratio of corporate debt significantly negative influence, profitability and liquidity does notaffect the timeliness of financial reports. In general it can be concluded that the financial statements only type variable that influence thetimeliness of financial reports. For further research is expected to use other variables that affect the timeliness offinancial reports.